INTEGRATED AHP AND FUZZY-PROMETHEE ON BEST SELECTION PROCESS - Rina Widyasari; Hendra Cipta; Ismail Husein (ZERO: Jurnal Sains, Matematika dan Terapan, 2018)
In best selection process such as best student, best employee, best destination, etc. need an effective method so it may have the best object in output. Criteria on each process consist of among qualitative variable and numeric variable. In fact, to make a decision we cant use our feeling but should use science method. In our research we offer integrated AHP (Analytical Hierarchical Process) and Fuzzy-Promethee to solve the selection process that has among categorical variable. The result show algorithm from integrated AHP and Fuzzy-Promethee.